Minor psychiatric disorders among nurses university faculties Disturbios psíquicos menores en enfermeros docentes universitarios Distúrbios psíquicos menores em enfermeiros docentes de universidades - Juliana Petri Tavares; Carmem Lúcia Colomé Beck; Tânia Solange Bosi de Souza Magnago; Roselaine Ruviaro Zanini; Liana Lautert (Universidade de São Paulo, 2012)
This cross-sectional study addresses 130 nursing faculty members in federal universities from Rio Grande do Sul, Brazil. It investigated the psychological demands and decision latitude (the Demand-Control Model by Karasek) and their association with Minor Psychological Disorders (MPDs). The Brazilian versions of the Self-Report-Questionnaire-20 and the Job Stress Scale were used. MPDs were prevalent in 20% of the studied individuals. After adjusting for potential confounders, the chances of participants presenting mental disorders were higher in the quadrant 'active strain jobs' (OR=14.23, 95% CI 1.55 to 130.73), followed by the 'high strain jobs' quadrant (OR=10.05, 95% CI 1.23 to 82.44), compared to nursing professors classified in the 'low strain jobs' quadrant. We conclude that high psychological demands and low control over work can cause disorders in nursing professors, among them, MPDs. Estudio epidemiológico seccional entre 130 enfermeros docentes de las universidades federales del estado de Rio Grande do Sul, en Brasil, que tuvo como objetivo investigar la demanda psicológica y el control del trabajo (Modelo Demanda-Control de Karasek) y sus asociaciones con Disturbios Psíquicos Menores. Se utilizaron las versiones brasileñas del Self-Report-Questionnaire-20 y del Job Stress Scale. La prevalencia de Disturbios Psíquicos Menores fue del 20,1%. Después de ajustar los posibles factores de confusión, las posibilidades de trastornos psíquicos fueron mayores en el cuadrante Trabajo Activo (OR=14,13; IC95%=1,55-130,73), seguido del cuadrante Alta exigencia (OR=10,05; IC95%=1,23-82,44), en comparación con los enfermeros docentes del cuadrante Baja Exigencia. Se concluyó que la alta demanda psicológica y el bajo control del trabajo pueden provocar daños a la salud, entre ellos los Disturbios Psíquicos Menores en enfermeros docentes. Trata-se de estudo epidemiológico seccional, incluindo 130 enfermeiros docentes das Universidades Federais do Rio Grande do Sul, Brasil, que teve por objetivo investigar a demanda psicológica e o controle sobre o trabalho (Modelo Demanda-Controle de Karasek) e sua associação com os distúrbios psíquicos menores. Foram utilizadas as versões brasileiras do Self-Report-Questionnaire-20 e da Job Stress Scale. A prevalência de distúrbios psíquicos menores foi de 20,1%. Após ajustes, a fim de se evitar potenciais confundidores, a chance de distúrbios psíquicos foi maior no quadrante trabalho ativo (OR=14,23; IC95%=1,55-130,73), seguido do quadrante alta exigência (OR=10,05; IC95%=1,23-82,44), quando comparado aos enfermeiros docentes do quadrante baixa exigência. Conclui-se que a alta demanda psicológica e o baixo controle sobre o trabalho podem desencadear acometimentos, dentre eles os distúrbios psíquicos menores em enfermeiros docentes.